2013
DOI: 10.1523/jneurosci.0363-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Fine-Scale Functional Correlation of Striate Cortex in Sighted and Blind People

Abstract: To what extent are spontaneous neural signals within striate cortex organized by vision? We examined the fine-scale pattern of striate cortex correlations within and between hemispheres in rest-state BOLD fMRI data from sighted and blind people. In the sighted, we find that corticocortico correlation is well modeled as a Gaussian point-spread function across millimeters of striate cortical surface, rather than degrees of visual angle. Blindness produces a subtle change in the pattern of fine-scale striate corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
90
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 62 publications
(5 reference statements)
13
90
2
Order By: Relevance
“…The cortical visual system extends far beyond this point, and blindness has been found to alter both the properties of these higher visual areas and the connections of visual cortex to other brain regions [25, 77, 78]. We regard the relationship between the anatomical variation we have measured and the properties of higher visual areas and their connections as a promising area for future study.…”
Section: Discussionmentioning
confidence: 95%
“…The cortical visual system extends far beyond this point, and blindness has been found to alter both the properties of these higher visual areas and the connections of visual cortex to other brain regions [25, 77, 78]. We regard the relationship between the anatomical variation we have measured and the properties of higher visual areas and their connections as a promising area for future study.…”
Section: Discussionmentioning
confidence: 95%
“…This observation is consistent with a study of resting state fMRI that reported decreased functional connectivity between the two occipital cortices in congenitally blind subjects (Liu et al, 2007). Butt et al (2013) found an alteration of the pattern of between-hemispheric striate correlation, but age of blindness onset had no impact on this parameter.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 97%
“…In visual cortex, regions selective for either foveal or peripheral stimuli, show correlated blood-oxygen level-dependent (BOLD) activity in anesthetized (7) and resting (8) monkeys. In human subjects, BOLD activity in visual areas is organized into highly specific maps (9-11), the organization of which reflect anatomy (12) and the specificity of which is affected by blindness (13). The finding of robust intrinsic networks using fMRI led to a large number of studies (14), which have recently demonstrated the functional importance of intrinsic networks.…”
mentioning
confidence: 99%